An Analysis of Coal Fly Ashes from Different Combustion Processes for The Agricultural Utilization - Farrah Fadhillah Hanum; Yudhi Pramudya; Firda Mahira Alfiata Chusna; Erda Rahmilaila Desfitri; Iqbal Hapsauqi; Nafira Alfi Zaini Amrillah (Green Engineering Society, 2023)
The residue of thermal power plants is known as coal fly ash and has been considered solid waste pollution worldwide. The characteristic of coal fly ashes showed that it contains several components that could be utilized in several fields. One of the potential utilization is in the agricultural application. This study analyzed the characteristic of two different types of coal fly ashes and their effect on the soil. The x-ray fluorescence (XRF) analysis resulted that SiO2, Al2O3, Fe2O3, CaO dan MgO are the five major components in the soil, and both coal fly ash, CFA A and CFA B. This XRF analysis result concluded that coal fly ashes have great potential to be a substitute for silica fertilizer. Then, the effect of the coal fly ash addition also was studied by the moisture content and nutrient (N, P, and K) content characteristics in the soil and the soil-ash mixture. The findings indicated that the addition of 125 grams of coal fly ash A had a greater impact on the soil compared to fly ash B when 250 grams of soil was used.